2021
DOI: 10.1021/acs.molpharmaceut.0c00961
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Macrophages Promote Oxaliplatin Resistance via METTL3-Mediated m6A of TRAF5 and Necroptosis in Colorectal Cancer

Abstract: As a third-generation platinum drug, oxaliplatin (OX) is widely used as the first-line chemotherapeutic agent in the treatment of colorectal cancer (CRC). CRC cells acquire resistance to chemotherapy and develop resistance, which is a major challenge for the treatment of advanced CRC. Recent studies have suggested that the therapeutic resistance of tumors is affected by the tumor microenvironment (TME). As a critical role among TME, tumor-associated macrophages (TAMs) play an important role. However, their reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 44 publications
0
55
0
Order By: Relevance
“…However, therapies targeting signaling pathways in pancreatic cancer lack efficacy due to the heterogeneity of tumor microenvironment (TME) in patients, TME prevents antitumor drug resistance, immune escape and tumor cell’s infiltration during cancer progression. Increasing evidence demonstrated that m6A modification is associated with TME of cancer, and the polarization of tumor-associated macrophages-M2 enabled the oxaliplatin resistance via the elevation of METTL3-mediated m6A modification [ 34 ]. Dali et al found a risen level of CD8+ cytotoxic T cells and natural killer (NK) cells while a reduced infiltration of myeloid-derived suppressor cells (MDSC) from Ythdf1−/− tumor mice compared to WT mice, besides, the therapeutic efficacy of PD-L1 checkpoint blockade is enhanced in Ythdf1−/− mice [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, therapies targeting signaling pathways in pancreatic cancer lack efficacy due to the heterogeneity of tumor microenvironment (TME) in patients, TME prevents antitumor drug resistance, immune escape and tumor cell’s infiltration during cancer progression. Increasing evidence demonstrated that m6A modification is associated with TME of cancer, and the polarization of tumor-associated macrophages-M2 enabled the oxaliplatin resistance via the elevation of METTL3-mediated m6A modification [ 34 ]. Dali et al found a risen level of CD8+ cytotoxic T cells and natural killer (NK) cells while a reduced infiltration of myeloid-derived suppressor cells (MDSC) from Ythdf1−/− tumor mice compared to WT mice, besides, the therapeutic efficacy of PD-L1 checkpoint blockade is enhanced in Ythdf1−/− mice [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…METTL3, as the most important writer of m 6 A, is upregulated in numerous malignancies and can epigenetically increase gene expression by specifically editing m 6 A sites modification, thus eliciting a potential malignant function ( 39 ). Previous studies have demonstrated that METTL3 is frequently upregulated in CRC, where it maintains high m 6 A modification levels ( 40 42 ). Consistently, the present data showed that METTL3 is elevated in five paired CRC tissues and CRC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…M2-polarized tumor-associated macrophages can elevate the level of m6A modification mediated by METTL3 and induce oxaliplatin (OX) resistance. Modulation of METTL3-mediated m6A modification may be a potential treatment strategy and molecular target for patients with OX resistance [32].…”
Section: Discussionmentioning
confidence: 99%